Effect of Postpartum Exercise and Oxytocin Massage on Uterine Involution among Postpartum Mothers - Novita Br Ginting Munthe; Iskandar Markus Sembiring; Rico Januar Sitorus (Journal of Epidemiology and Public Health, 2026)
Background: Uterine involution is an essential physiological process following childbirth that restores the uterus to its pre-pregnancy size and function. When this process is delayed or incomplete, it can lead to postpartum complications such as hemorrhage. Postpartum exercise and oxytocin massage are non-pharmacological interventions widely believed to accelerate uterine recovery and reduce the risk of complications. Subjects and Method: This quantitative pre-experimental study with a pre-test and post-test without control design was conducted at Klinik Pratama Matahari, Tanjung Morawa, Deli Serdang, North Sumatra, Indonesia, from February to July 2025. Twenty postpartum mothers were selected using purposive sampling and divided into two groups: 10 received postpartum exercise and 10 received oxytocin massage. Uterine involution was assessed by fundal height observation before and after intervention. Data were analyzed using t-tests with a significance level of p < 0.05. Results: Most respondents were aged 26–30 years (50.0%), had a senior high school education (50.0%), and were unemployed (75.0%). Before the interventions, all participants (100%) had abnormal uterine involution. After the interventions, 70% of mothers in the postpartum-exercise group and 50% in the oxytocin-massage group achieved normal uterine involution. Statistical analysis indicated significant improvements in both groups, with a stronger effect in the postpartum-exercise group (mean difference= 0.70; p= 0.001) than in the oxytocin-massage group (mean difference = 0.50; p = 0.025). Conclusion: Both postpartum exercise and oxytocin massage effectively enhanced uterine involution among postpartum mothers, with postpartum exercise demonstrating greater effectiveness. These findings support the integration of structured postpartum exercise programs into routine maternal care to promote uterine recovery and prevent postpartum complications.